Cronbach’s alpha in mathematics education research: Its appropriateness, overuse, and alternatives in estimating scale reliability - Zakariya, Yusuf F. (Frontiers in Psychology, 2022)
Critiques of coefficient alpha as an estimate of reliability coefficient and internal consistency of scale items are widespread in the literature. However, the continuous overuse of this statistic in mathematics education research suggests a disconnect between theory and practice. As such, this article argues, in a non-technical way, for the limited usefulness of coefficient alpha, its overuse, and its alternatives in estimating scale reliability. Coefficient alpha gives information only about the degree of the interrelatedness of a set of items that measure a construct. Contrary to the widely circulated misconceptions in mathematics education research, a high coefficient alpha value does not mean the instrument is reliable and does not imply the instrument measures a single construct. Coefficient alpha can only be dependable as an estimate of reliability under verifiable and restrictive conditions. I expose these conditions and present steps for their verification in empirical studies. I discuss some alternatives to coefficient alpha with references to non-technical articles where worked examples and programming codes are available. I hope this exposition will influence the practices of mathematics education researchers regarding evidence of the reliability of research instruments.